Microsoft Encarta interactive world atlas 2001 (Microsoft Corp., 2000)
Offers 1.8 million place names plus in-depth country articles with unique cultural information. Users can choose from more than 21 different maps styles, add or remove place names, borders, and topographic detail to create custom maps for reports and presentations.